Disability, Labour Inclusion and Social Marketing in Spain: The ONCE Foundation Case. - Cruz-Morato, Marco Antonio; Dueñas-Zambrana, Carmen (Springer Nature, 2021)
Labour inclusion for people with disabilities and its impact on the quality of life of this group, in economies such as Spain, is still a problem. In spite of the previous efforts carried out by policy makers based on regulation, the situation persists and it seems necessary to confront it in a different way. Thus, in this work, Social Marketing and Behavioral Economics are presented as powerful tools to overcome the problem, fighting against the social stigma usually suffered by people with disabilities, and it also describes how NGOs, associations and society as a whole can participate in finding the solution. The ONCE Foundation campaigns “Don’t be my limit” and “Working is a story” are described according to this model. The study of successful cases and the potential of Social Marketing (from a Behavioral Economics approach) to tackle the exclusion of people with disabilities in the labour market could be a very interesting starting point to promote actions oriented in this sense, and to ensure a more sustainable and prosperous future for everyone in terms of quality of life.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Personas con discapacidad - Empleo; Fundación ONCE; Disability; Labour inclusion; Social marketing; Behavioral economics; Social exclusion